Women In The World Of Modeling As An Inspiration For Creating Fine Art Paintings - Triani Sartika, Ni Nyoman; Gulendra, I Wayan; Jodog, I Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
This study explores how the female body is represented in the visual world of fashion as a source of inspiration in the creation of paintings that highlight female figures by emphasizing aesthetic and symbolic aspects. The representation of the female body in the modeling world is not merely a physical expression but also carries cultural constructions, ideologies, and complex social narratives related to women’s identity, roles, and existence in society. Within this approach, the body is understood as a space of expression that embodies grace, strength, and gentleness, as well as vulnerability, which can be transformed into a visual language in art. The research applies a practice-based creative exploration method, involving stages of visual observation, technical experimentation, and critical reflection on issues of bodily representation in visual art. The Sigar Mangsi technique, a distinctive Balinese painting tradition, is combined with the use of Chinese ink and acrylic paint to create expressive visual compositions. This combination of media symbolizes the duality of strength and fragility in the female body, visualized through metaphors such as insect fibers, wings, and butterfly forms as symbols of transformation and freedom. The resulting works depict female figures in artistic costumes rendered on canvas, presenting both glamorous and reflective nuances while contributing to the development of contemporary painting rooted in local wisdom. This study not only produces aesthetically engaging visual forms but also opens critical discourse on the body, beauty, identity, and symbolism in visual art, thereby enriching perspectives on the relationship between art, fashion, culture, and painting.